EFEKTIVITAS PENGGUNAAN PROGRAM SISTEM INFORMASI KESEJAHTERAAN SOSIAL NEXT GENERATION (SIKS-NG) BERBASIS E-GOVERNMENT DI DINAS SOSIAL KABUPATEN SRAGEN - Yulfa, Shelfiyana; Suhita, Damayanti (Solidaritas, 2025)
AbstractThe Next Generation Social Welfare Information System (SIKS-NG) program is an application used by the Sragen Regency Social Service in e-government-based poverty data collection. This application aims to simplify the poverty data collection process and produce data summaries, such as recapitulation, data improvement, and proposals for new data. However, in its implementation there are still obstacles, one of which is the lack of understanding of human resources regarding technology, thus hampering the optimization of the use of SIKS-NG. This study uses Budiani's theory (2007) which refers to four indicators, namely Target Accuracy, Program Socialization, Program Objectives, and Program Monitoring. The purpose of this study is to determine the effectiveness of the use of the e-government-based SIKS-NG Program in the Sragen Regency Social Service. The method applied in this study is descriptive qualitative with a purposive sampling technique for selecting informants. Data collection was carried out through interviews, observations, and documentation, while data analysis refers to the theory of Miles, Huberman, and Saldana (2014:14). The results of the study indicate that the effectiveness of the use of the SIKS-NG Program based on the four indicators varies. Target accuracy is considered less effective due to human error in implementation in the field. Program socialization is also still not optimal because several obstacles are still found. Meanwhile, the program objectives are considered to have run well, and program monitoring is considered effective. Therefore, it is necessary to increase the understanding of officers regarding the program mechanism and strengthen socialization so that the implementation of SIKS-NG can run more optimally and be categorized as a fully effective program.Keywords: SIKS-NG Application, Program Effectiveness, E-Government